NURSES' PROFESSIONAL COMPETENCE COMPONENTS SELF-ASSESSMENT IN BUILDING A POSITIVE HEALTH CARE ENVIRONMENT - Miķelsone, Madara; Renigere, Ruta; Dreimane, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Nurses' professional competence consists of several interrelated components, which during interacting of critical thinking, reflection and experience, characterizes the essence of the profession of nurses. Critical thinking applies not only to the educational process, it is an expression the nurses’ responsible and professional action during the health care process. Critical thinking and reflection make up of various specific competence component interactions of nurses professional healthcare process. The professional competence of the nurse grows and develops in interaction of social, educational and health care environment, learning process, and is realized in the context of the knowledge and experience. It is constantly exposed to the transformation from the potential state to the actual, developing, increasing its potential and readiness in a systemic perspective.The study aims to determine the self-assessment level of the nurses' professional competence components to create a positive environment for health care and improve health care quality.It is important for nurses to engage in scientific research work, thus developing evidence-based health-care practices. Research task in nursing and health care is the identification and development of knowledge, promoting the use of the theory of nursing in practice through critical and systematic way of thinking and implementing the theory based health care. The study utilized: 1) nurses' professional competence component self-assessment scale (Nurse Competence Scale); 2) The research process implementation barrier assessment scale (Barrier scale).